Interspecies politics and the global rat: Ecology, extermination, experiment. Issue 2 (April 2023) - Youatt, Rafi
Abstract: Rats tend to thrive wherever humans do. In recent centuries, the growth of human populations around the planet has meant the growth of a nearly equivalent global population of rats, particularly in cities, where they thrive on trash, food scraps, and infrastructure, and widely stymie human efforts to get rid of them. This forced coexistence has inspired a wide range of human responses, ranging from revulsion and extermination efforts as vermin, to religious veneration and use as experimental lab animals. At the same time, the political figure of the rat has played a constitutive role in violence and experimentation against human populations who are deemed as rat-like. To understand these linked dynamics, the article frames the idea of interspecies internationality, against both Anthropocene and geopolitical readings of the planetary condition. It then elaborates three axes around which rat assemblages have been formed – exterminative, experimental, and ecological. The article concludes by arguing that the rat, as interspecies figure of politics and as living creature, allows us to understand important dynamics around the generation of disposable life, political difference, and conditions of coexistence, in ways that are critical to the entwined politics of life on the planet.